Investigating tradeoffs between competing agricultural objectives using multi-objective optimization under uncertainty - Margarit, Philip; Doherty, John; Ludtke, Leslie; Nieber, John; Wilson, Bruce; Magner, Joseph (Frontiers in Environmental Science, 2025)
Management of groundwater quality in agricultural areas requires tradeoffs between competing objectives. These objectives include economic benefit, respect for regulatory-imposed water quality standards, and an equitable distribution of revenue that is foregone in order to meet these standards. It also requires recognition of the fact that the calculated outcomes of a proposed management strategy are accompanied by uncertainty. In this study, we apply formal multi-objective optimization under uncertainty to investigate these tradeoffs as they apply to nitrate-N leaching rates in the northern Pineland Sand Aquifer System in Central Minnesota. This region is important both to agricultural producers and the Anishinaabe Peoples of White Earth Nation. The methodologies that we demonstrate exemplify a scientific framework in which simulation-based, management-pertinent analyses can support negotiations between different stakeholder groups wherein the risks and consequences associated with different management strategies are clearly delineated. At the same time, it is able to advance stakeholder understanding of the environmental factors that are salient to optimal groundwater management, and the necessity to accept uncertainty, and hence risk, when exploring management options. It also provides insights into sources of uncertainty, and strategies that can most effectively reduce it.